2012
DOI: 10.1021/ol300942z
|View full text |Cite
|
Sign up to set email alerts
|

Fluoreno[4,3-c]fluorene: A Closed-Shell, Fully Conjugated Hydrocarbon

Abstract: The synthesis and optoelectronic properties of 24 π-electron, formally antiaromatic 4,11-di-t-butyl-1,8-dimesitylfluoreno[4,3-c]fluorene (FF) are presented. The solid-state structure shows that the outer rings are aromatic, while the central four rings possess a bond-localized 2,6-naphthoquinone dimethide motif (in red). The biradical character of FF is assessed experimentally and computationally; the results of which implicate a closed-shell ground state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 22 publications
1
49
0
Order By: Relevance
“…The first system explored using transient absorption spectroscopy in solution was fluoreno[4,3-c]fluorene derivative 1a [10]. The initial absorptive feature that appears at approximately 675-800 nm (Figure 2a) is likely related to the S 2 state, as the calculated S 0 -S 1 transition is forbidden in this system (vide infra).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first system explored using transient absorption spectroscopy in solution was fluoreno[4,3-c]fluorene derivative 1a [10]. The initial absorptive feature that appears at approximately 675-800 nm (Figure 2a) is likely related to the S 2 state, as the calculated S 0 -S 1 transition is forbidden in this system (vide infra).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous small-molecule systems have been developed toward this goal that employ extended pi-conjugated centers [5][6][7][8][9]. One such molecular class of interest is the p-quinodimethane-containing indenofluorenes and related molecules (e.g., 1-3, Figure 1), which have recently been realized through synthesis [10][11][12][13][14][15][16][17]. Intriguingly, these compounds have been found to be non-emissive and thus we wished to examine their photophysics.…”
Section: Introductionmentioning
confidence: 99%
“…(Scheme ) . Since this first example of reductive dearomatization using SnCl 2 , a wide variety of substituted [1,2‐ b ]IFs and [1,2‐ b ]IF analogues including indeno[2,1‐ c ]fluorene 63 , fluoreno[4,3‐ c ]fluorene 64 , diindeno[1,2‐ b :2′,1′‐ n ]perylene 65 , and heteroatom‐containing derivatives 66 a – d , and 67 a – c have been realized (Figure ) . While early research demonstrated IFs 62 – 65 contained a nonaromatic para ‐xylylene core, the Haley lab has recently shown that substituting or replacing the outer ring of the [1,2‐ b ]IF with thiophene ( 66 a and 67 a ) or benzothiophene ( 66 c , d and 67 b , c ) dramatically increases the antiaromaticity of the s ‐indacene core.…”
Section: Snii‐mediated Reduction Of Diolsmentioning
confidence: 99%
“…(Scheme 23). [110] Since this first example of reductive dearomatization using SnCl 2 ,awide variety of substituted [1,2-b]IFs [111] and [1,2-b]IF analogues including indeno[2,1-c]fluorene 63, [112] fluoreno[4,3-c]fluorene 64, [113] diindeno[1,2-b:2',1'n]perylene 65, [114] andh eteroatom-containing derivatives 66 ad,a nd 67 a-c have been realized ( Figure 8). [115] While early research demonstrated IFs 62-65 contained an onaromatic paraxylylene core, [110,112,114] Scheme23.…”
Section: Acid-free Sn II -Mediated Reductiono Fdiolsmentioning
confidence: 99%
“…[14] We have examined alternative IF geometries such as the [2,1-c] isomer (e.g., 10). [15] We can dearomatize expanded central cores such as naphthalene (e.g., 11) [16] and thienoacenes (e.g., 12). [17] We have studied their redox chemistry [11] and photophysics [8] as well as made forays into materials applications.…”
mentioning
confidence: 99%